Sosialisasi, Literasi dan Implementasi Produk Perbankan Syariah - Mohammad Rizal; Arini Fitria Mustapita; Arista Fauzi Kartika Sari; Dewi Diah Fakhriyyah; Ahsani Taqwiem (Universitas Serang Raya, 2022)
The banking world is currently experiencing rapid growth, new banks have emerged such as Islamic banks, so it is inevitable that a competitive and tight banking business will emerge. This service activity is expected to provide provisions for the participants, so that they can improve the Islamic economy. Understanding of Islamic banking products will provide benefits for them in terms of the Islamic economy. The systematics of the implementation of this service activity are Socialization, Literacy and Implementation with the assisted subjects who are partners of this community service activity are Karang Taruna and Dinoyo Residents in Lowokwaru District, Malang City. The activity is carried out in three stages, namely problem identification, activity implementation, and implementation evaluation. The result of the implementation of this activity was that the Participants expressed their gratitude to us for being given the opportunity to take part in the Islamic banking literacy and socialization activities so that they could open their minds who had so far felt that conventional banks and Islamic banks were the same. This shows that the literacy and socialization of Islamic banking in society is still not active enough so that activities like this should be carried out more frequently.